Molecular characterization of Giardia duodenalis in Yemen - Alyousefi, N.A.; Mahdy, M.A.K.; Xiao, L.H.; Mahmud, R.; Lim, Y.A.L. (2013)
Giardia duodenalis is an important intestinal protozoan in Yemen with infection rates ranging from 18 to 27. To date, there has been no genotyping study to provide a better understanding of the transmission dynamic. This study was conducted to genotype and subtype G. duodenalis in Yemen. Stool samples were collected from 503 Yemeni outpatients between I and 80 years old, including 219 males and 284 females. Giardia cysts were detected via microscopy after the formal-ether concentration. Genotyping of Giardia was carried out using PCR and sequence analysis of the 16s rRNA and b-giardin genes. Of the 89 microscopy-positive Giardia samples, 65 were successfully sequenced, of which 66 (43 of 65) were identified as G. duodenalis assemblage A and 34 (22 of 65) as assemblage B. Further subtyping analysis based on b-giardin gene identified the presence of subtypes A2 and A3, which belong to the anthroponotic sub-assemblage All. Data of the study suggest that anthroponotic transmission played a potential role in the transmission of giardiasis in the community. However, further genotyping and subtyping studies of specimens from humans and animals living in the same households are needed for a more definitive understanding of giardiasis transmission in Yemen. (C) 2013 Elsevier Inc. All rights reserved.